Barriers and enablers to the adoption of practices to improve crop production and reduce vulnerability to climate risks in the semi-arid Omusati Region,Namibia - Chappel, Angela (Department of Environmental and Geographical Science, 2019)
Namibia is almost entirely semi-arid or arid. With evaporation rates being higher than precipitation rates, farming conditions are extremely adverse. This is exacerbated by the impacts of climate change, namely increased temperature, decreased rainfall and higher rainfall variability, all of which are projected to worsen in the future. More than half of the population is reliant on rain-fed subsistence agriculture for their source of food but these challenging conditions mean that there is widespread food insecurity across the subsistence farming community in Namibia. This leads to a state of vulnerability and dependence on government support in the form of social grants, food aid and remittances from family members in urban areas. The locus for this study is three villages: Omaenene, Okathitukeengombe and Oshihau, in the north-central Omusati region of Namibia. This research investigated local perceptions of climate change vulnerability, farming practices used in other regions that could reduce this vulnerability and finally barriers and enablers to the uptake of new farming practices. These objectives were answered through the use of a systematic literature review and interviews with the local community. Findings revealed that the local population is already experiencing a hotter and drier climate, which has decreased their yield output. Many farmers are concerned about future climatic changes while some are comforted by support from the government or God. In both of these cases, the farmers are vulnerable because they are not currently adapting or planning to adapt to climate change. Although a majority of the farmers claimed that they are willing to try new farming practices, they are inhibited by: limited access to new information, mistrust of new farming practices as well as insufficient labour and resources. Three adaptive farming practices – planting pits, bunds and composting – aimed predominantly at water harvesting, soil conservation and increasing soil quality were selected by the researcher, from a systematic literature review, as appropriate for the village sites. Some of the social and institutional enablers that could be enhanced to promote the uptake of these practices are: i) support from local authorities and possibly enlisting the help of religious and traditional leaders (including building trust within these networks), ii) enhancing information access predominantly through the radio, iii) explaining the severity of climate change and the value of adaptation practices, iv) establishing self-help labour groups and v) the creation of demonstrations sites. In the face of irreversible climate change, this research aims to contribute to empowering local people to adapt their farming practices to the harmful experienced and predicted impacts of climate change and climate variability.